Cascading renal injury after brain death: Unveiling glycocalyx alteration and the potential protective role of tacrolimus - Idouz, Kaoutar; Belhaj, Asmae; Rondelet, Benoit; Dewachter, Laurence; Flamion, Bruno; Kirschvink, Nathalie; Dogné, Sophie (Frontiers in Cell and Developmental Biology, 2024)
Brain death (BD) is a complex medical state that triggers systemic disturbances and a cascade of pathophysiological processes. This condition significantly impairs both kidney function and structural integrity, thereby presenting considerable challenges to graft viability and the long-term success of transplantation endeavors. Tacrolimus (FK506), an immunosuppressive drug, was used in this study to assess its impact as a pretreatment on brain death-induced renal injury.This study aimed to investigate changes associated with brain death-induced renal injury in a 4-monthold female porcine model. The experimental groups included brain death placebo-pretreated (BD; n=9), brain death tacrolimus-pretreated using the clinical dose of 0.25 mg/kg the day before surgery, followed by 0.05 mg/kg/day one hour before the procedure (BD + FK506; n=8), and control (ctrl, n=7) piglets, which did not undergo brain death induction. Furthermore, we aimed to assess the effect of FK506 on these renal alterations through graft preconditioning. We hypothesized that immunosuppressive properties of FK506 reduce tissue inflammation and preserve the glycocalyx.Our findings revealed a series of interconnected events triggered by BD, leading to a deterioration of renal function and increased proteinuria, increased apoptosis in the vessels, glomeruli and tubules, significant leukocyte infiltration into renal tissue, and degradation of the glycocalyx in comparison with ctrl group. Importantly, treatment with FK506 demonstrated significant efficacy in attenuating these adverse effects. FK506 helped reduce apoptosis, maintain glycocalyx integrity, regulate neutrophil infiltration, and mitigate renal injury following BD . This study offers new insights into the pathophysiology of BD-induced renal injury, emphasizing the potential of FK506 pretreatment as a promising therapeutic intervention for organ preservation, through maintaining endothelial function with the additional benefit of limiting the risk of rejection.